Relationship between HR Practices & Employee Turnover Intentions by Taking Moderating Effect of Neuroticism and Extroversion.: Empirical Analysis of Selected Banks from Pakistan - Danial Akhtar Sumbal (SEISENSE (PRIVATE) LIMITED, 2018)
The study is an association study because the relationship between employee turnover intentions and HR practices is studied by taking moderation effect of neuroticism and extroversion. The hypotheses are tested by taking Banking Industry in context of Pakistan. This tested the relationship of different independent factors (HR practices) with employee turnover intentions, the major causes among them, and the magnifying effect of neuroticism and extroversion, and its significance thereon. Data is collected through self-administered questionnaires and is analyzed by using different analytical techniques in SPSS including regression analysis, principal component analysis and descriptive statistics.